Green hay application and diverse seeding approaches to restore grazed lowland meadows: progress after 4 years and effects of a flood risk gradient. (11th August 2020) - Wagner, Markus; Hulmes, Lucy; Hulmes, Sarah; Nowakowski, Marek; Redhead, John W.; Pywell, Richard F.
Abstract : The two most common approaches to target species introduction in European meadow restoration are green‐hay transfer from species‐rich donor sites and the use of diverse seed mixtures reflecting the chosen target community. The potential of both approaches to restore species‐rich grassland has been variously reviewed, but very few studies have experimentally compared them at one and the same site. Moreover, studies involving one or both approaches have rarely taken into account environmental gradients at a site, and measured the impacts of such gradients on restoration outcomes. Such gradients do, for example, exist during grassland restoration on former arable land in river floodplains, where gradients in the occurrence of flooding, and in associated edaphic characteristics such as nutrient availability, might affect restoration outcomes. Using a randomized complete block experimental design, based on five different indicators of restoration progress, we compared the usefulness of green‐hay application and diverse seeding to restore species‐rich grazed meadows of the MG5 grassland type according to the British National Vegetation Classification, and also investigated how restoration outcomes differed after 4 years between areas within experimental plots characterized by high flood risk and areas characterized by low flood risk. Overall, both restoration approaches yielded similar results over the course of the experiment, whereas high flood risk and associated edaphic factors such as high availability of phosphorus negatively affected restoration progress particularly in terms of floristic similarity to restoration targets. These results highlight the need to take into account environmental gradients during meadow restoration.